Determination of Polycyclic Aromatic Hydrocarbons in Soil Sample Using Matrix Solid Phase Dispersion-Stable Isotope Dilution Technique-Gas Chromatography Mass Spectrometry - Zhang, Y.T.; Zhang, L.; Zhao, G.X.; Zhang, G.Q.; Zuo, H.Y.; Li, X.Y.; Gui, J.Y. (Asian Journal of Chemistry, 2012)
A method was developed for the determination of polycyclic aromatic hydrocarbons (PAHs) in soil sample by measuring stable isotope dilution technique of matrix solid-phase dispersion extraction-gas chromatography mass spectrometry. The sample adopted silica with bonded C18 as solid supports, used dichloromethane-acetone to elute and realized cleaning and recovery. The research verified the similar physicochemical properties and the consistency of chromatographic behaviour between target compounds and compounds containing deuterium, confirmed that isotope fractionation was not obvious during the sample pretreatment in this experiment. The recovery of standard addition was between 97.5 to 109.2 %, the precision was between 0.89 and 3.06 % and achieved satisfactory recovery.